Narrative, Gender and Marginality: The Case Study of Ella Lauchner Smith - Tye, Diane (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1991)
When Ella L. Smith joined the history department of Mount Allison University during World War II, she was one of the few women on faculty and was soon to become the only female acting department head of her day. After her retirement from teaching, Smith remained an active member of the university community, managing a campus book store. Throughout her lifetime Ella Smith represented one of Mount Allison’s most colourful characters. Part of the university’s narrative repertoire continues to celebrate her comments. This paper examines in retrospect some of these narratives told about Smith, both for what they reveal of her role within the university community, and of larger societal attitudes towards women who entered what was then very much the male world of university teaching.